2021
DOI: 10.3390/genes12091459
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Avian Testis Development

Abstract: As in other vertebrates, avian testes are the site of spermatogenesis and androgen production. The paired testes of birds differentiate during embryogenesis, first marked by the development of pre-Sertoli cells in the gonadal primordium and their condensation into seminiferous cords. Germ cells become enclosed in these cords and enter mitotic arrest, while steroidogenic Leydig cells subsequently differentiate around the cords. This review describes our current understanding of avian testis development at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 216 publications
(331 reference statements)
0
14
0
Order By: Relevance
“…Anti-Müllerian hormone (AMH) is expressed at low levels from the same time point, either directly or indirectly activated by DMRT1. The crucial testis factor SOX9 is first expressed later (at E6.0/stage 29) at the onset of testis cord organization ( Estermann et al, 2021b ). Gonadal TOX3 expression more closely resembles that of SOX9.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-Müllerian hormone (AMH) is expressed at low levels from the same time point, either directly or indirectly activated by DMRT1. The crucial testis factor SOX9 is first expressed later (at E6.0/stage 29) at the onset of testis cord organization ( Estermann et al, 2021b ). Gonadal TOX3 expression more closely resembles that of SOX9.…”
Section: Resultsmentioning
confidence: 99%
“…Male germ‐cell differentiation is controlled by various signal transduction and transcription factors and strongly dependent on surrounding somatic gonadal cells after their sex differentiation [ 3 , 4 ]. Although various signaling pathways are involved in the development of chicken germ cells [ 11 , 21 ], studies on the mechanisms regulating mitotically arrested male germ cells are lacking [ 22 ]. In this study, we identified signaling pathways involved in mitotic arrest and subsequent quiescent state of male germ cells by single‐cell transcriptome analysis of germ cells isolated from a germ‐cell tracing chicken model.…”
Section: Discussionmentioning
confidence: 99%
“…So far, research on circRNAs has mainly focused on humans and model animals, and less research has been carried out on testicular development. Like other vertebrates, the avian testis is the site of spermatogenesis and androgen production, and research on testicular biology in avians mainly focuses on chickens and ducks ( Estermann et al, 2021 ). Research on circRNA in poultry mainly focuses on muscle cell proliferation and differentiation ( Ouyang et al, 2018 ; Shen X. X. et al, 2019 ), follicle development ( Shen M. M. et al, 2020 ; Wu et al, 2020 ), disease and immunity ( Qiu et al, 2018 ; Wang et al, 2020 ) and intramuscular fat deposition ( Wang, 2018 ).…”
Section: Discussionmentioning
confidence: 99%